Comparative Analysis of Chinese Language Proficiency Assessment: A Case Study of AP and IGCSE Examinations - Peng, Meiqi (Ilmu Inovasi Nusantara, 2024)
With the growing global interest in learning Chinese, the proliferation of Chinese language exams by various institutions has become evident. This paper delves into a comparative analysis of the assessment systems of the College Board's AP Chinese Language and Culture Examination and the Cambridge IGCSE Chinese Examination across five dimensions: score categorization, paper composition, assessment methods, exam syllabus arrangement, and evaluation principles. The study aims to identify similarities and differences between the two exams and draw insights for language testing and assessment practices. The findings reveal that both exams provide valuable educational experiences and insights. Recommendations include refining assessment systems to comprehensively evaluate candidates' language proficiency, integrating cultural elements into examination materials, and leveraging modern technological means to enhance fairness in language testing and assessment processes.